Penggunaan Aplikasi Mobile Technology untuk Deteksi Breeding Place Pencegahan Demam Dengue: Literature Review - Agni Laili Perdani; Ratna Nurul Komariah; Dewi Srinatania (Risenologi, 2021)
The existence of a breeding place have threefold greater risk to the DHF incidence. The participation of mosquito monitoring interpreters (JUMANTIK) by using an Android-based smartphone application functions play significant role to inform the location of interactive breeding places with the latest data updates. Aim of this study to analyze the use of mobile technology applications in the detection of dengue breeding places with the PRISMA method approach. Method used in this study is s a literature review . Database used Google Scholar, Pubmed and Proquest. The keywords used are the combination "mobile technology application", "breeding place", "dengue". Inclusion criteria are articles published in 2016- 2020, using English or Indonesian and have full text. The advantages of the android application are very effective, low cost in controlling mosquito larvae, recent monitor, record and track the location of the existence of breeding places. The innovation are needed to design android specifications that are more organized in data collection of respondents to facilitate Jumantik's work in determining the breeding place coordinator.